Comorbidities and medication intake among people with dementia living in long-term care facilities - Marques, Alda (2015)
Information on comorbidities and medication of people with dementia (PWD) in longterm-facilities (LTF) is scarce. This study analysed type and number of comorbidities and medication of PWD in LTF. A descriptive-study was conducted in 40 LTF, characterising 329 PWD. Socio-demographics, dementia type, comorbidities and medication were collected with International-Classification-of-Functionality-checklist. Cognitive impairment was assessed with Mini-Mental-State-Examination. One or more comorbidities (2.1 ± 1.6) were found in 271 participants. Hypertension, osteoarticular-problems, heart-disease and type-II-diabetes were the frequently comorbidities. 327 participants consumed one or more medicines (7.3 ± 3.2), mainly for cardiovascular system, anxiolytics and antipsychotics. Comorbidities and medication amount was significantly different among cognitive impairment levels. Vascular comorbidities were present in all dementia types.